Psychosocial Issues in Long-Term Survivors of Testicular Cancer - Schepisi, Giuseppe; De Padova, Silvia; De Lisi, Delia; Casadei, Chiara; Meggiolaro, Elena; Ruffilli, Federica; Rosti, Giovanni; Lolli, Cristian; Ravaglia, Giorgia; Conteduca, Vincenza; Farolfi, Alberto; Grassi, Luigi; et al. (Frontiers in Endocrinology, 2019)
Testicular cancer is the most frequent tumor in young males aged 15 to 39 years. As cure rates are currently around 90%, the prevalence of survivors is increasing. However, a disease-free condition does not necessarily correspond to a life free of physical and psychosocial health problems. The aim of this review was to explore psychosocial morbidity among testicular cancer survivors. A literature search was conducted in three electronic databases (PubMed, Medline and Embase). The results of the search on cancer survivors were then combined with those of the search on psychosocial concerns and work performance. Eighty-four publications met the inclusion criteria. Physical, psychological, work-related problems and changing perspectives about work and life in general influenced life and career decisions among testicular cancer survivors. Individual health, sexual relationships and work problems, affect several important aspects of survival and significantly influence the QoL of long-term survivors.